Educational Technologies aimed at promoting parental care of premature newborns at home: an integrative review - Luciana Ribeiro de Carvalho; Marcelo Victor Freitas Nascimento; Marcia Teles de Oliveira Gouveia; Carla Daniele Araújo Feitosa (Revista de Enfermagem da UFPI)
Objective: To identify scientific evidence about Educational Technologies aimed at promoting parental care of premature newborns at home. Methods: Integrative review based on primary studies published in full, in all languages, with no defined time frame, in the following databases: National Library of Medicine; Scopus, Web of Science, Embase and Biblioteca Virtual em Saúde Brasil. The articles were screened using the Rayyan application. The included studies were duly read and entered into the Red Internacional de Enfermería en Salud Ocupacional form, from which the following data were extracted: author, year of publication, country, language, specifications of the target group, study design, level of evidence, objective, type of technology and outcome. The analysis of the results was based on Merhy's classification of technologies. Results: Of the twenty-two studies included in the review, there was a predominance of educational technologies categorized as Smartphone apps, in addition to thematic educational approaches based on relationships. Twenty-one technologies met the needs of the study participants satisfactorily, and only one revealed insecurity among the target audience. Conclusion: Educational Technologies were vital to support the transition of premature babies from hospital to home and served as an instrument aimed at promoting care, with a high level ...